Behaviour and distribution of wild geese in south-east Scotland - Newton, I; Thom, V M; Brotherston, W (Wildfowl, 1973)
In southeast Scotland immigrant Greylag and Pink-footed Geese fed entirely on farmland (including grassland), where their distribution was governed by the location of suitable roosts, from which they flew to restricted feeding areas nearby. Continual movement took place between different roosts, and peak numbers occurred in different months in different districts. Pinkfeet preferred the safer of a range of sites for roosting, including estuaries, large lakes and reservoirs, and remote moorland pools, while Greylag also used less safe sites, including small ponds and rivers. Of forty-five major goose roosts in the study area, only nine were used regularly by both species, the rest by one or other. On shared roosts the two species kept apart. Pinkfeet were also more particular in their choice of feeding areas, and often foraged further from their roosts than did Greylag. Greylag rarely flew more than 5 km to feed, but Pinkfeet regularly more than 10 km, and occasionally more than 20 km. Differences in roosting and flighting habits led to spatial separation of the two species on farmland and, of the total goose country in the study area, only 13% was occupied by both species together, the rest by one or other. Within limits set by the location of suitable roosting and feeding areas, the distribution of geese, was influenced mainly by disturbance, especially shooting.